Exploring the Role of Vertical and Horizontal Pathways in the Formation of Lettuce Plant Endospheric Bacterial Communities: A Comparative Study of Hydroponic and Soil Systems - Polina Kuryntseva; Nataliya Pronovich; Gulnaz Galieva; Polina Galitskaya; Svetlana Selivanovskaya (Horticulturae, 2025)
Plant-associated microbiomes play a critical role in plant health, nutrition, growth, and adaptation. This study aimed to investigate the formation pathways of the endospheric microbiome in lettuce (Lactuca sativa) through vertical (seed) and horizontal (substrate) transmission in hydroponic and soil environments. The bacterial microbiomes from the seeds, roots, leaves, and substrates were analyzed via 16S rRNA gene sequencing. The seed microbiome contained 236 OTUs dominated by Verrucomicrobia (31%) and Firmicutes (29%). Rhizospheric soil contained 1594 OTUs, while the hydroponic solution had 448 OTUs. The root endosphere from soil-grown lettuce contained 295 OTUs, compared with 177 in hydroponic conditions, and the leaf microbiome contained 43 OTUs in soil and 115 OTUs in hydroponics. In total, 30–51% of the leaf and root microbiomes originated from the seed microbiota, while 53–65% of the root microbiome originated from the substrate. Microbiome overlap was observed between the rhizospheric soil and the root microbiome. This study provides new insights into the microbiome of lettuce seeds and the pathways of formation of the endospheric microbiome in adult plants. These findings lay the groundwork for future research aimed at better understanding microbiome dynamics in leafy crops and plant protection.